Red Star over the Pacific, Revised Edition China's Rise and the Challenge to U.S. Maritime Strategy. - Yoshihara, Toshi (Naval Institute Press, 2018)
This is an assessment of how the rise of Chinese seapower will affect U.S. maritimes strategy in Asia.